2012
DOI: 10.5539/ijef.v4n11p51
|View full text |Cite
|
Sign up to set email alerts
|

Market Share and Cash Policy: Evidence from Western European Companies

Abstract: This study analyses the impact of market share on corporate cash policy in a static as well as a dynamic framework. Using a panel data set of large firms in 14 European countries, we show that firms with high market share tend to have lower cash holdings. This relationship between market share and cash policy is most apparent when predation risk, measured using either the similarity of a firm's technology with its industry rivals or market concentration, is high. These findings are robust for different estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…= 0.000). The results of this survey is consistent with findings of Schoubben and Van Hulle (2012) where they reported a reverse and meaningful relationship between size of the firm and cash holding. The results are also consistent with findings of Ferreira and Vilela (2004) who reported that cash holdings were positively influenced by the investment opportunity set and cash flows and negatively influenced by asset's liquidity, leverage and size.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…= 0.000). The results of this survey is consistent with findings of Schoubben and Van Hulle (2012) where they reported a reverse and meaningful relationship between size of the firm and cash holding. The results are also consistent with findings of Ferreira and Vilela (2004) who reported that cash holdings were positively influenced by the investment opportunity set and cash flows and negatively influenced by asset's liquidity, leverage and size.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, they reported that investment-q; sensitivity and investment speed were highest in oligopolistic industries, implying that the value of investing strategically could outweigh the value of waiting. Schoubben and Van Hulle (2012) investigated the effect of market share on corporate cash policy in a static as well as a dynamic framework based on a panel data set of large firms in 14 European countries. They reported that firms with high market share could have lower cash holdings.…”
Section: Introductionmentioning
confidence: 99%